PENGARUH LINGKUNGAN KERJA PEGAWAI TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA PT. PLN (Persero) DISTRIBUSI LAMPUNG AREA TANJUNG KARANG - Agustuti Handayani (e-JKPP, 2019)
This research is a quantitative research regression analysis, the population in this study are all employees at PT. PLN (PERSERO) Distribution Lampung Tanjung Karang area, amounting to 70 employees. The instrument used is a questionnaire with a Likert scale that has 5 alternative answers. Test the validity of the instrument using item analysis and calculated using the product moment formula, while the reliability test uses the Croncbach's Alpha formula. Then the hypothesis test uses a partial test.The results of the study are: (1) the level of goodness of the work environment at PT. PLN (PERSERO) Distribution Lampung Area Tanjung Karang is in the good category of 63% of 100%. (2) the level of goodness of work effectiveness at PT. PLN (PERSERO) Distribution Lampung Tanjung Karang Area in the good category of 61% of 100%. (3) There is a positive and significant influence between the work environment and the work effectiveness of employees at PT. PLN (PERSERO) Distribution Lampung Tanjung Karang Area with a determination coefficient of 0.8262 which means that 82.62% of the work effectiveness of employees is influenced by the work environment at PT. PLN (PERSERO) Distribution Lampung Tanjung Karang Area. And the remaining 17.38% is explained by other factors.